A Dictionary of Pali, Part I, A-Kh. Margaret Cone. - Norman, K. R. (Buddhist Studies Review, 2001)
A Dictionary of Pali, Part I, A-Kh. Margaret Cone. Pali Text Society, Oxford 2001. xxiv, 778 pp. £25.00. ISBN 0 86013 394 X.